Comparative study on 16s rRNA gene Sequences for clinical and environmental isolates of legionella pneumophila. - Mohammed Alani; Ibrahim Alani (مجلة جامعة الانبار للعلوم الصرفة)
This study aimed to identify and describe the identity and phylogenetic position of two Legionella pneumophila isolates from Falluja, Iraq: one clinical (M1) was isolated from a patient with pneumonia symptoms, and one environmental (H1) was isolated from the surface of a potable water pipe close-ended by the same researchers as this study. This study examined the genetic patterns of 16S rRNA gene sequences at one genetic locus. Direct sequencing of amplified segments was used to determine the genetic variability of bacterial samples. Afterward, a thorough and precise tree was built to test the reported variants' phylogenetic positions and discrimination. It was determined by aligning the M1 sample's nucleic acid sequences with Legionella pneumophila's reference sequences (GenBank acc. no. KF537568.1), which had the highest homology. identified two nucleic acid variations (141A>G and 247T>C) not seen in this reference sequence. The tree analysis showed that the M1 sample was in a distinct evolutionary position and matched numerous European strains. The M1 sample was likewise assumed to have come from the same tree as the other strains, including H1. The nucleic acid variations in the M1 sample changed its phylogenetic position within Legionella pneumophila's clades. The presence of H1 samples near many non-clinical strains showed that the ribosomal RNA used could identify the isolation source. The current study demonstrated that 16S rRNA sequences may identify Legionella pneumophila sequences in samples. This genetic locus can be used to detect additional bacterial phylogenetic distributions.